2021
DOI: 10.2196/26628
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning–Based Prediction of Growth in Confirmed COVID-19 Infection Cases in 114 Countries Using Metrics of Nonpharmaceutical Interventions and Cultural Dimensions: Model Development and Validation

Abstract: Background National governments worldwide have implemented nonpharmaceutical interventions to control the COVID-19 pandemic and mitigate its effects. Objective The aim of this study was to investigate the prediction of future daily national confirmed COVID-19 infection growth—the percentage change in total cumulative cases—across 14 days for 114 countries using nonpharmaceutical intervention metrics and cultural dimension metrics, which are indicative of specific nation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 74 publications
0
19
0
1
Order By: Relevance
“…Ayyoubzadeh et al analyzed the rate of COVID-19 incidence in Iran using Google Trends data and deep learning methods [ 14 ]. Yeung et al combined several online COVID-19 data to train and evaluate five nontime series machine learning models in predicting confirmed infection growth [ 15 ]. These studies have shown that AI is suitable for evaluating disease trends and can provide governments with information that can be used to prevent outspread.…”
Section: Introductionmentioning
confidence: 99%
“…Ayyoubzadeh et al analyzed the rate of COVID-19 incidence in Iran using Google Trends data and deep learning methods [ 14 ]. Yeung et al combined several online COVID-19 data to train and evaluate five nontime series machine learning models in predicting confirmed infection growth [ 15 ]. These studies have shown that AI is suitable for evaluating disease trends and can provide governments with information that can be used to prevent outspread.…”
Section: Introductionmentioning
confidence: 99%
“…A different line of work replaces epidemiological models with machine learning methods to directly predict the number of new infections [22][23][24][25]. Importantly, Yeung et al [26] added non-pharmaceutical interventions (policies) as features in their models; however, their approach is limited to make predictions up to two weeks in advance, since information about the policies that will be implemented in the future is not available at inference time. Our SIMLR approach differs by being interpretable and also by forecasting policy changes, which allows it to extend the horizon of the ∆I predictions.…”
Section: Related Workmentioning
confidence: 99%
“…Namun, model tersebut biasanya tidak menggambarkan interaksi dan hubungan non-linear [24]. Seiring perkembangan bidang Artificial Intelligence terus meningkat seperti penggunaan machine learning techniques untuk membantu pekerjaan manusia [25] serta permasalahan pada model statistik linear. Machine learning techniques dapat menjadi salah satu pilihan dalam prakiraan kualitas udara seperti yang telah dilakukan Mahajan dkk [26] menggunakan model Exponential Smoothing (ES) untuk melakukan prakiraan terhadap PM, serta membandingkannya dengan beberapa model seperti ARIMA, NNAR, dan ANN (Hybrid).…”
Section: Pendahuluanunclassified